Binders, Materials and Technologies in Modern Construction VII - Dvořák Karel; Gazdiĉ Dominik (Trans Tech Publications, 2021)
This volume contains extended papers presented at the 19th International Conference on Silicate Binders (ICBM 2020), held on 3 December 2020 in Brno, Chech Republic. The conference was focused on scientific and practical achievements in the development and properties research of inorganic binders for building materials. The most important topics were related to the investigation of cementitious composites and other hydraulic and silicate binders and analysis of lime and gypsum-based binders' chemical properties and production technologies. We hope that these proceedings will be helpful to many professionals in the field of building materials.